Menahan Amarah sebagai Bentuk Pengendalian Diri dalam Pandangan Hadis - Ademas Muhammad Alawi; Nazwa Amalia; Zaeni Anwar; Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss about holding back anger in the view of hadith. This study uses an approach approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about anger control in the history of Ahmad No. 2817. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi quality that meets the qualifications of maqbul ma'mul bih for the Islamic experience. This study concludes that the hadith narrated by Ahmad No. 5840 is relevant as understanding and knowledge of anger control for self-development.